2019
DOI: 10.1186/s40711-019-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in the elderly in Mexico, challenges to the public policies

Abstract: The National Council for the Evaluation of Social Development Policy (CONEVAL 2018) reports that 7.8% of the population in Mexico is 65 years old or older. Approximately 41.1% of this population lives in poverty, 34.6% lives in moderate poverty, and 6.6% lives in extreme poverty. While previous research has discussed the impact of poverty and loneliness on psychological development and well-being (Mayer, F. David, Ecología económica de lacapacidad cognitiva. 2010; Montero-López Lena, María, Pobreza como Dolor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Quality of marriage has been argued to be a multidimensional construct consisting of both positive factors (such as spousal support) and negative factors (such as spousal strain), which may co-occur in relationships (Walen & Lachman, 2000). The relevance of spousal support is expected given past studies of the beneficial effects of social support in preventing loneliness (Montero-López Lena et al, 2019;Rodrigues et al, 2014), yet prior studies have found that both spousal support and strain may be independently related with loneliness in couples. In studies of older adults in the United States, support from a spouse has been related with less loneliness, whereas spousal strain tended to increase loneliness (Ayalon et al, 2013;Chen & Feeley, 2014).…”
Section: Loneliness In Marriagementioning
confidence: 99%
“…Quality of marriage has been argued to be a multidimensional construct consisting of both positive factors (such as spousal support) and negative factors (such as spousal strain), which may co-occur in relationships (Walen & Lachman, 2000). The relevance of spousal support is expected given past studies of the beneficial effects of social support in preventing loneliness (Montero-López Lena et al, 2019;Rodrigues et al, 2014), yet prior studies have found that both spousal support and strain may be independently related with loneliness in couples. In studies of older adults in the United States, support from a spouse has been related with less loneliness, whereas spousal strain tended to increase loneliness (Ayalon et al, 2013;Chen & Feeley, 2014).…”
Section: Loneliness In Marriagementioning
confidence: 99%
“…The most striking result was that in Mexico, loneliness was not significantly associated with any emotion. A previous study revealed that in Mexico, the negative effect of loneliness on mental health was attenuated when there were social interactions and family support (Lena et al, 2019). In our study, only 0.75% of Mexican participants were living alone, which may somehow be related to the relevance of family ties in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, la ansiedad fue extremadamente severa para todos los participantes del estudio, indistintamente su edad. Hallazgo que se pone a favor de la determinación de que la ansiedad puede ser un factor que afecta la salud mental de las personas en cualquier etapa de la vida (15,16) . Uno de los descubrimientos de mayor relevancia dentro del estudio fue la determinación de que el estrés y la depresión afectó severamente al personal médico, de enfermería, a los técnicos de emergencia y los auxiliares; lo que evidencia que los servidores de la salud que atendieron en primera línea en tiempos de pandemia fueron los que mayormente sufrieron afecciones en su salud mental.…”
Section: Discussionunclassified